Validation of the Chefs’ Key Competencies Questionnaire: A Culinary Student Perspective - Mahfud, Tuatul; Nugraheni, Mutiara; Pardjono; Lastariwati, Badraningsih (Journal of Technical Education and Training, 2020)
The chef is considered a success factor for culinary tourism. Hence, mastering the chefs’ key competencies through culinary schools is very important. Many studies have examined chef competencies, but we have not yet discovered how to measure the chefs’ key competencies according to culinary student perceptions. This study involved 392 culinary students in public vocational high schools. Data was collected by proportional random sampling through a questionnaire distributed to seven public vocational schools in Yogyakarta, Indonesia. Questionnaire validation used three techniques, namely, content validity test with Aiken V analysis, small sample validity test with Pearson correlation analysis, and finally, CFA analysis. This study shows that culinary students’ perceptions of chefs’ key competencies can be explained by indicators of creativity, culinary skills, hygiene & food safety, aesthetics, business sense, interpersonal, managerial, and leadership. Chefs’ Key Competencies Questionnaire (CKCQ) consists of 30 items consisting of creative (3 items), culinary skills (5 items), hygiene & food safety (4 items), aesthetics (2 items), business sense (4 items), interpersonal (3 items), managerial (4 items), and leadership (5 items). All items (30 items) have good validity and reliability values. The findings of this study discuss in-depth and some implications for vocational education practitioners proposed for further improvement. VET practitioners can also use this questionnaire to evaluate the achievement of the chefs’ key competencies of culinary students and professional chefs.